Optimalisasi Peningkatan Daya Saing UMKM Kuliner Medan melalui Digitalisasi Pemasaran dan Manajemen Keuangan Kota Medan - Purnama Sari, Dian; Vina Winda Sari; Ekawati, Yuni Andri; Akbar, Aswin; Muhammad Syahrizal (JPM: Jurnal Pengabdian Masyarakat, 2025)
This community engagement program aims to enhance the competitiveness of culinary micro, small, and medium enterprises (MSMEs) in Medan City through training in digital marketing and basic financial management. A preliminary survey of 20 MSMEs revealed that most lacked strategic use of social media and did not maintain proper financial records. The program was implemented through interactive training and field mentoring over two months. The results showed significant improvements in four key areas: social media usage increased from 50% to 85%, financial record-keeping from 20% to 75%, digital literacy from 30% to 85%, and financial literacy from 25% to 75%. Participants also reported increased business revenue and enhanced online promotion skills. The program aligns with prior research findings while offering a unique approach through integrated methods and tangible behavioral change among participants. Limitations include a relatively short implementation period and the absence of long-term impact assessment. Nevertheless, the program is considered successful and has the potential to be replicated for other MSME sectors with a more sustainable strategy.